Integration of Local Wisdom in Strategic Management of Higher Education: Findings of a Multi-Site Study - M. Alang Khairun Nizar Bin Ismail; Amiruddin Siahaan; Yusuf Hadijaya (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study examines strategic management of higher education institutions based on local wisdom through a qualitative multisite approach. The research was conducted at Institut Jam’iyah Mahmudiyah (IJM) Langkat and STKIP Budidaya Binjai, two private higher education institutions that explicitly integrate local values into their institutional governance. Using in-depth interviews, participant observation, and document analysis, this study explores how local wisdom is embedded in strategy formulation, implementation, and evaluation. The findings reveal that local wisdom functions as strategic capital that shapes institutional identity, leadership orientation, organizational culture, and quality assurance mechanisms. IJM Langkat grounds its strategy in historical–ideological legitimacy rooted in Islamic–Malay traditions, while STKIP Budidaya Binjai adopts a sociological–pragmatic approach emphasizing social relevance and graduate character. Despite these differences, both institutions successfully translate local wisdom into teaching, research, community service, and student development practices. Strategy evaluation further demonstrates that culturally grounded quality assurance enhances both managerial accountability and moral legitimacy. This study contributes to the discourse on higher education management by positioning local wisdom as a dynamic, context-sensitive resource for sustainable institutional competitiveness.